PENGARUH CITRA MEREK, KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUTUSAN MENGINAP DI FAVE HOTEL AHMAD YANI BEKASI - Jenti Rosalina; Parlagutan Silitonga (Panorama Nusantara, 2018)
This study aims to determine and analyze the influence of brand image, service quality, and location on the decision to stay at Fave Hotel Ahmad Yani Bekasi. The population in this study were guests who stayed at Fave Ahmad Yani Bekasi in the period May to July 2018. The sampling technique used non probability sampling, with the Slovin method to determine 100 respondents. Data collection method uses a questionnaire that has been tested for validation and reliability. The analytical method uses the Clasic test, before Multiple Linear Regresion by SPSS 20.00. The 100 respondents as a tool, followed by F, t, Correlation and Determination Test. The results of the study prove that partially, the brand image variable does not significantly influence the decision to stay, the variable service quality has a significant effect on the decision to stay and the location variable has a significant effect on the decision to stay at Fave Hotel Ahmad Yani Bekasi. And of all these variables simultaneously have a significant effect on the decision to stay at Fave Hotel Ahmad Yani Bekasi